2011
DOI: 10.1002/iub.446
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and formation of endogenous histidine hexa‐coordination in cold‐adapted hemoglobins

Abstract: Spectroscopic and crystallographic evidence of endogenous (His) ligation at the sixth coordination site of the heme iron has been reported for monomeric, dimeric, and tetrameric hemoglobins (Hbs) in both ferrous (hemochrome) and ferric (hemichrome) oxidation states. In particular, the ferric bis- histidyl adduct represents a common accessible ordered state for the β chains of all tetrameric Hbs isolated from Antarctic and sub-Antarctic fish. Indeed, the crystal structures of known tetrameric Hbs in the bis-His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…[14] Studies carriedo ut in the last two decades have clearly shown that these Hbs are endowedw ith an increased level of flexibility that allows them to adopt structural states that are not easily accessible to mammalian Hbs. [15] Indeed, it has been shown that these Hbs easily adopt, when well folded, av ariety of oxidationa nd structuralf orms such as hemichromes [16][17][18][19] and oxidized pentacoordinate states, [11,20] which are more rarely found in mammalian Hbs, [21] but more frequently in monomeric Hbs. [22] This varietyo fc oordination states frequentlyp roduces some peculiar structural motifs at both tertiary-and quaternary-structure levels.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Studies carriedo ut in the last two decades have clearly shown that these Hbs are endowedw ith an increased level of flexibility that allows them to adopt structural states that are not easily accessible to mammalian Hbs. [15] Indeed, it has been shown that these Hbs easily adopt, when well folded, av ariety of oxidationa nd structuralf orms such as hemichromes [16][17][18][19] and oxidized pentacoordinate states, [11,20] which are more rarely found in mammalian Hbs, [21] but more frequently in monomeric Hbs. [22] This varietyo fc oordination states frequentlyp roduces some peculiar structural motifs at both tertiary-and quaternary-structure levels.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present an additional experiment-generated source of denitrosylation owing to X-ray photolysis of crystals of nitrosylated Hb from the Antarctic fish Trematomus bernacchii (HbTb). Crystal structures of HbTb are available in several ferrous (Camardella et al, 1992;Mazzarella et al, 2006) and ferric forms (Vergara et al, 2007(Vergara et al, , 2009Merlino et al, 2011) at different pH values. Indeed, this system represents a model for the study of the peculiarities of fish Hb [such as the Root effect (Verde et al, 2008) and haemichrome formation (Verde et al, 2008;Vitagliano et al, 2008;Merlino et al, 2011)].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a Tyr (probably TyrB10) is the internal ligand coordinated to the heme iron and not the distal HisCD1, as might be expected. In general, the ferric bis‐histidyl adduct is the common state for the β chains of all tetrameric Hbs isolated from Antarctic and sub‐Antarctic fish, and in various monomeric Hbs of different origins . However, although the most probable sixth ligand is a His residue, the internal Tyr coordination of the heme iron has been previously observed also in other truncated Hbs .…”
Section: Discussionmentioning
confidence: 83%